Kuantitas Total Bakteri Coliform pada Instalasi Pengolahan Limbah Cair Medis Laboratorium Klinik - Indah Sulistiyawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Health service activities at the Clinical Laboratory produce infectious and non-infectious waste in the form of solid or liquid. Clinical laboratory liquid waste is one source of environmental pollution if the concentration exceeds the standard quality of wastewater. Polluted water quality parameters include microbiologics of Coli / Total Coliform Germs. Water quality with microbiological parameters can be used to determine the presence of bacteria, viruses, parasites. Bacteria used as indicators are Coliform bacteria. At present several clinical laboratories have implemented a Liquid Wastewater Treatment Plant. So that the waste discharged into the environment meets the standard quality standards for hospital liquid waste, and minimal pollution. This study aims to determine the quantity of Total Coliform at the inlet and outlet points of the Wastewater Treatment Plant Laboratory Medical Liquid. The results showed that the quantity of Total Coliform at the inlet sampling point of the liquid media waste at the Wastewater Treatment Plant Laboratory reached the highest value > 1.6 x 105 MPN / 100 ml, and after processing at the Wastewater Treatment Plant Laboratory decreased to 0 MPN / 100 ml (no coliform was found ), and with the highest value of 2.7 x 103 MPN / 100 ml, according to the waste water quality standard.